Spatially uneven development and low carbon transitions: Insights from urban and regional planning - Balta-Ozkan, Nazmiye; Watson, Tom; Mocca, Elisabetta (Cranfield University, 2015)
The ageing of existing energy system infrastructure, the threat of climate change and uncertainty in the movement of energy prices have resulted in a widespread agreement on the need for a transition to a low carbon energy system. Yet the nature of this transition (i.e. what, when, how and where) and its socio-economic outcomes at different scales are not well understood. The interdependence of the energy sector and economic growth has been mostly studied at the national level (via some general equilibrium or econometric models) whilst sub-national studies at community or urban levels mostly focus on the governance of transitions. Hence, we suggest that a regional perspective to energy policy and research promises to integrate these two approaches by providing a more robust and comprehensive understanding of the implications of low carbon transitions, as well as contributing to the development of more effective policies. By building on recent ideas on geographical aspects of energy transitions, this article offers insights on the changing relationship between the spatial organisation of economic activities and energy systems, and identifies tools and methods from urban and regional planning to help with the delivery of efficient and equitable policy outcomes.
Keywords: Low carbon transition; Smart grid; Regional science; Regional energy transition